Possibilities of essential phospholipids in alcoholic liver disease of terminal stage - M. A. Butov; A. S. Vasilevskaya (Медицинский совет, 2016)
Essential phospholipids (Essentiale Forte N, Aventis, France-Germany) in alcohol-associated hepatic cirrhosis improve the subjective state of patients, reduce manifestations of asthenic and dyspeptic syndromes, intensity of jaundice, have a positive effect on biochemical indicators of cytolysis and cholestasis. The conducted clinical study showed effectiveness of use of essential phospholipids as hepatoprotective agents for hepatic diseases of alcoholic etiology.